Teachers’ perception of the factors influential on teacher-student relationship: A phenomenological analysis - Narjes Lāri; Elāhe Hejāzi; Javad Ejei; Bahram Jowkar (فصلنامه نوآوری‌های آموزشی, 2019)
Teacher-student relationship is not just a simple interaction between its two sides, but rather a complete transaction that is formed in a context of the effective factors. This study aimed to understand the factors influencing this relationship from the teachers’ point of view. It was a qualitative research with phenomenological design, which tried to describe these factors, deeply. Participants included 19 primary school teachers (12 females, 7 males) selected from public primary schools in Shirāz city through purposive sampling method and they participated in the semi-structured interviews. The teachers’ viewpoint about the students’ classroom behaviors and specific characteristics that are important for their relationship, the classroom trajectories that can be used to communicate with the students, factors outside the teacher/student circle, which affect their relationship with each other, and the qualities of the teachers’ mood, beliefs and motivation that augment their relationship with the students were extracted as findings of this study. These components made it possible to get comprehensive dimensions of the teachers’ viewpoints on this research’s concern. The results could explain the possible substrates for the positive intervention in a student-teacher relationship.